The Effectiveness of a Psychological Guidance Rehabilitative Program Accompanied by EMG Technology for the Adductor Muscles of the Thighs on Muscular Strength and Emotional Arousal in Injured Football Players - Dr. Mushtaq Khadhim Mohammed (Zien Journals, 2026)
The Effectiveness of a Psychological Counseling and Rehabilitation Program Combined with EMG Technique for the Adductor Muscles of the Thighs on Muscle Strength and Emotional Arousal in Injured Football Players
Keywords: Guidance program; psychological rehabilitation; EMG technique